Immune-mediated diseases and thromboembolic events: a modified Delphi panel. (3rd August 2021) - Azimi, Nassir; Caldera, Freddy; Cohen, Stan; Conners, James; Fernandes, Timothy; Han, May; Strand, Vibeke; Tapson, Victor; Weinberg, Aaron; Weinberg, Jeffrey; Yarur, Andres
Abstract: Introduction: A multidisciplinary panel of physicians was convened to gain understanding of the relationship between thromboembolic events (TEs) and immune-mediated diseases (IMDs). The primary objective of the panel was to assess areas of consensus on the IMD most prone to TE as well as modifiable and unmodifiable factors that might exacerbate or mitigate the risk of TEs. Methods: Thirteen nationally recognized physicians were selected based on their contributions to guidelines, publications and patient care. The modified Delphi panel consisted of four rounds of engagement: (1) a semi-structured interview, (2) an expert panel questionnaire, (3) an in-person panel discussion, and (4) a consensus statement survey. Results: Ulcerative colitis and Crohn's disease were identified as two of four IMDs with the highest TE risk. Consensus was reached on several non-modifiable and modifiable characteristics of high-risk. Approaches to reduce TE incidence were identified such as altering treatment, requiring the monitoring of patients for TEs and modifying patient behaviors. Janus kinase inhibitors and corticosteroids were identified as therapies that required further evaluation given their potential TE risk. Discussion: The panel reached a consensus that several IMDs are at an elevated risk of TEs. Physicians are unable to control most patient level risk factors but can control the therapies being used. Consequently, physicians should consider the specific IMD, be aware of TE risk factors, and take into account risk factors in selecting the therapies to optimally manage their conditions and to reduce the risk of TEs in this population.